A Concurrent Estimation of Phytoconstituents Piperine, Quercetin and Kaempferol Present in Siddha Polyherbal Formulation Kabasara Kudineer by Rp-Hplc - T. Devisri (International Journal of Antibiotics, 2024)
A straightforward, accurate, and precise technique was developed and validated for the simultaneous determination of Quercetin, Kaempferol, and Piperine in the polyherbal formulation Kabasura Kudineer. The sample was chromatographed using a C18 column (150x4.6mm, 5u) with a mobile phase composed of Acetonitrile and Ortho phosphoric acid in a 45:55 ratio, flowing through the column at a rate of 1ml/min. The detection wavelength for Quercetin, Kaempferol, and Piperine was set at 254 nm. The retention times for Quercetin, Kaempferol, and Piperine were determined to be 3.2 mins, 4.4 mins, and 13.4 mins, respectively. The precision, as indicated by the % RSD for Quercetin, Kaempferol, and Piperine, was found to be within acceptable limits. The LOD and LOQ values for Quercetin, Kaempferol, and Piperine were also within acceptable limits. The correlation coefficient for the three phytoconstituents was calculated to be 0.999.
Keywords: Kabasura Kudineer; Piperine; RP-HPLC; kaempferol; quercetin